Public Finance : Theory and Approach - N Radhakrishnan (Delhi Vrinda Publications Pvt Ltd, 2019)
Public Finance-Theory and Approach is a comprehensive textbook based on UGC model curriculum and broad based on the syllabus of public finance of leading Indian universities at their UG and PG level the book has been divided into nine modules .
Keywords: Public Sector and Allocation of Resources; Public Revenue; Public Debt; Fiscal Policy; Fiscal Federalism; Budget